DESIGN, SYNTHESIS AND BIOLOGICAL EVALUATION OF SOME NEW SUCCINIMIDE, 2-IMINOTHIAZOLINE AND OXAZINE DERIVATIVES BASED BENZOPYRONE AS ANTICONVULSANT AGENTS - El-ansary, Sohair L.; Hassan, Ghaneya S.; Rahman, Doaa E. Abdel; Farag, Nahla A.; Hamed, Mohammed I.; Baset, Marawan A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of the present study was to synthesize novel benzopyrone derivatives with potential and safer anticonvulsant activity. Methods: New benzopyrone derivatives have been synthesized and characterized by spectral and elemental analysis. These compounds tested for anticonvulsant activity using the maximal electroshock (MES) and subcutaneous pentylenetetrazole (scPTZ) screens (phase 1), which are the most widely employed seizure models for early identification of new anticonvulsant agents. Phase 2 including, neurotoxicity screening and quantitative determination of the median effective dose (ED50), median lethal dose (LD50) and protective index (PI) for the active compounds from phase 1. Results: Compound 12b possessed potent anticonvulsant activity with ED50 values of 94.75 and 70.7 mg/kg in the MES and scPTZ screens respectively, and had LD50 value of 2546 mg/kg after intraperitoneal injection to mice, which provide compound 12b with a wide protective index of 26.87 and 36.01 for MES and scPTZ screens respectively compared to the reference drug Phenobarbital with PI of 12.16 and 20.08, respectively. In addition, compound 12b exhibited mild neurotoxicity at the maximum administrated dose (200 mg/kg). Conclusion: Compound 12b possessed broad spectrum activity for the treatment of all types of seizures, with a wide protective index compared to Phenobarbital. Consequently, compound 12b can be selected as a new bio candidate lead for further study. Keywords: Benzopyrone, Succinimide, 2-Iminothiazoline, Oxazine; Anticonvulsant.